Managing Stakeholder Dialogue: The Case of Botnia in Uruguay. (June 2013) - Heikkinen, Anna; Kujala, Johanna; Lehtimäki, Hanna
Stakeholder dialogue is an effective way for a company to enhance its sensitivity to the operational environment and to increase stakeholders' understandings of the dilemmas facing the company. An open and transparent dialogue process can create fertile ground for solving tensions in stakeholder relations. However, the process is not always straightforward. This article presents a case where a Finnish forest industry company's decision to build a pulp mill in Uruguay raised both opposing and supporting views among the local interest groups. The company faced the challenge of how to engage with the hostile, opposing groups in order to ensure their operations in Uruguay. By engaging in this case, students will deepen their understanding of the multitude of stakeholder interests and learn to facilitate a dialogue that seeks to find solutions and avoid conflict in a situation of a stakeholder dispute.